Colonization After Emancipation : Lincoln and the Movement for Black Resettlement - Magness, Phillip W. (Book collections on Project MUSE., 2011)
"Colonization after Emancipation reveals an unexplored chapter of the Emancipation story. A valuable contribution to Lincoln studies and Civil War history, this book unearths the facts about an ill-fated project and illuminates just how complex, even convoluted, Abraham Lincoln's ideas about the end of slavery really were"--Jacket flap.